Product recall effectiveness and consumers' participation in corrective actions - Sascha Raithel; Stefan J. Hock; Alexander Mafael (Journal of the Academy of Marketing Science, 2023)
Firms struggle to respond to product recalls and achieve high recall effectiveness, i.e., the percentage of affected consumers who participate in corrective actions. We present the first comprehensive study of recall effectiveness that analyzes a broader set of product categories, identifies managerially relevant drivers, outlines boundary conditions, and demonstrates the underlying psychological processes. Specifically, three studies investigate the impact of remedy choice, incident likelihood, and their interaction with firm reputation on recall effectiveness. In Study 1 (unique secondary data set), we show that remedy choice and incident likelihood each interact with the firm's reputation to influence recall effectiveness. In two subsequent experiments, we not only test the findings of the secondary data in a causal setting but also examine the underlying psychological process. We find that offering full remedy leads to higher recall effectiveness for high reputation firms and that recall effectiveness is higher for recalls with a high incident likelihood, but only for high reputation firms. In both cases, firms not only make consumers feel like they would benefit more from participating in the recall, but they also make them feel more comfortable in their ability to participate in the recall. These nuanced findings enable us to derive actionable guidelines for firms to increase recall effectiveness.
Keywords: 330; Product recall; Product recall effectiveness; Recall compliance; Health belief model